Bicyclic lactams derived from serine or cysteine and 2-methylpropanal - Bagum, H; Shire, BR; Christensen, KE; Genov, M; Pretsch, A; Pretsch, D; Moloney, MG (Thieme Publishing, 2020)
Bicyclic lactams may be prepared from serine or cysteine and 2-methylpropanal; the resulting S,N-heterocycles are more stable than the corresponding O,N-heterocycles but both are synthetic intermediates capable of further elaboration.